Teaching Preschoolers Theory of Mind Skills With Mobile Games - Nikolayev, Mariya; Evmenova, Anya S.; Reich, Stephanie M.; Clark, Kevin A.; Burns, M. Susan (Frontiers in Education, 2022)
This single-case research study examined whether an interactive, touch screen app enriched with language (e.g., mental state verbs and syntactic structures) known to promote theory of mind (ToM) interactions in face-to-face settings could enhance ToM skills in preschoolers. Six typically developing girls between the ages of 46 and 52 months participated in multiple sessions across the three phases of the study: In baseline, children played games without voice-overs; in the original treatment phase, participants played games with embedded voice-overs; finally, in the modified treatment phase, participants first played games with embedded voice-overs, then participated in the researcher-led discussion. All sessions across the three phases concluded with ToM the assessments. ToM was assessed with two measures based on a continuous scale: the first measure included three tasks and targeted earlier-developing ToM skills (diverse desires, diverse beliefs, and knowledge access), and the other measure had two tasks that assessed later-developing ToM competency, false belief understanding. The functional relation between children’s earlier-developing ToM skills, i.e., understanding that people have different desires, beliefs, and knowledge access, and voice-overs in digital games, was observed only when the gameplay was followed by a discussion about the game content with a researcher. No evidence of functional relation between children’s later-developing ToM skills - false belief- and mental state language voice-overs in digital games was observed under any treatment phases. These results indicate that incorporating ToM conducive language in digital games can promote ToM improvements, especially when supplemented by an adult-led conversation.